Uji Karakteristik Enzim Lipase Dari Biji Nyamplung (Calophyllum Inophyllum L) Sebagai Media Pembelajaran Biokimia dalam Bentuk Buletin - Hakim, Aliefman; Burhanuddin, Burhanuddin; Juniarly, Lalu Anugrah Dimas (FKIP University of Mataram, 2025)
This study aimed to develop a biochemistry learning media derived from experimental research on the characterization of lipase enzymes extracted from Calophyllum inophyllum (nyamplung) seeds. The development process employed a Research and Development (R&D) approach, adopting the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The study was limited to the development phase. The learning media was evaluated through two primary dimensions: validity and practicality. Data collection involved the distribution of expert validation instruments to subject-matter lecturers and practicality response instruments to students via Google Forms. A purposive sampling technique was employed, targeting Chemistry Education students from the 2020 and 2021 cohorts who had enrolled in the Biochemistry I course. A total of 30 students were randomly selected from this pool. The validity assessment conducted by expert validators yielded a score of 90.5%, indicating that the media falls within the